Comparison of efficacy and post-operative complications of adenotonsillectomy using coblation versus adenotonsillectomy using microdebrider and bipolar diathermy - Sureshkumar, Sethulakshmi; Hamza, Nesva Pilaparambil; Francis, Abhilash Alex (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Adenotonsillectomy is one of the widely performed surgical procedures in children worldwide, but there continues to be no universally accepted “ideal” method of tonsillectomy. This study is aimed to compare the outcome of coblation adenotonsillectomy versus microdebrider adenoidectomy with bipolar tonsillectomy in terms of efficacy and complication rate. Methods: In this analytical observational study, 40 patients who underwent adenotonsillectomy were divided into two groups according to the technique of surgery adopted. Group A were the children who underwent coblation adenotonsillectomy and group B underwent microdebrider adenoidectomy with bipolar tonsillectomy. Comparison was made between intraoperative bleeding, the method of haemostasis, ease of haemostasis during surgery, post operative pain and comfort levels of the patient and also recurrence of symptoms after 3 months. Results: Results of this study show that microdebrider adenoidectomy was found to have significantly higher intraoperative bleeding. The surgeons found it easier to attain hemostasis in the group who underwent coblation adenotonsillectomy. Postoperative pain, pain while feeding, difficulty in talking, higher rates of residual adenoid tissue were observed more in adenotonsillectomy using microdebrider and bipolar diathermy while ear pain, edema of the uvula were found to be slightly higher with coblation adenotonsillectomy. Conclusions: Results of our study conclude that ‘coblation adenotonsillectomy’ has an advantage over ‘adenotonsillectomy using microdebrider and bipolar diathermy’ and was found to be more efficacious and safer with less morbidity and rapid recovery.